Handbook on supercritical fluids : fundamentals, properties and applications - Osborne, Jane (Physics research and technology., 2014)
Supercritical fluid carbon dioxide (sc-CO2) possesses both gas-like and liquid-like properties. It is capable of depositing nanoparticles in small structures and poorly wettable substrates. Deposition and array formation of metal and metal sulfide nanoparticles on various substrates using sc-CO2 as a medium has been a subject of considerable interest for researchers in nanomaterials area in recent years. This handbook begins by exploring nanoparticle deposition using supercritical fluid carbon dioxide. Further topics in this handbook include separation of oils using supercritical carbon dioxid.